2009
DOI: 10.1504/ijbis.2009.022823
|View full text |Cite
|
Sign up to set email alerts
|

Role of mobile technology in the construction industry – a case study

Abstract: The construction industry is facing a number of pressures to decrease costs, improve productivity and have a competitive edge in terms of quality of service and customer satisfaction. Recent advancements in mobile technology provide new avenues for addressing this situation. This paper presents the role of emerging mobile technologies and, in particular, the development of a mobile facsimile solution that assists collaborative communications between parties on or away from the construction site. This paper fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Although the basis of analysis covered a very small survey sample, it provided a starting point for encouraging further uptake of multiple mobile technologies in the sector. Venkatraman & Yoong (2009) developed a mobile facsimile application, called ClikiFax, to facilitate image-based messaging to a smart phone or fax machine and collaborate time-critical information among contractors, architects, and owners, at remote construction sites. As evident from literature, ubiquitous technologies enable new functionalities from the early design phase to the very end of an asset's life cycle, in real time, irrespective of location (Gerbert et al, 2016).…”
Section: Ubiquitous Digital Accessmentioning
confidence: 99%
“…Although the basis of analysis covered a very small survey sample, it provided a starting point for encouraging further uptake of multiple mobile technologies in the sector. Venkatraman & Yoong (2009) developed a mobile facsimile application, called ClikiFax, to facilitate image-based messaging to a smart phone or fax machine and collaborate time-critical information among contractors, architects, and owners, at remote construction sites. As evident from literature, ubiquitous technologies enable new functionalities from the early design phase to the very end of an asset's life cycle, in real time, irrespective of location (Gerbert et al, 2016).…”
Section: Ubiquitous Digital Accessmentioning
confidence: 99%
“…Research in this area can be grouped into two major categories: the first one addresses the status and prospects of utilizing mobile technology in the construction industry as well as industry needs and challenges faced [11,15,17]. The second one focuses on reporting the development of mobile computing tools and their implementation at construction sites [4,18]. Atalah and Seymour [11] surveyed the current state of wireless information technology in the construction industry and reported that the level of interest in wireless technology is much higher than the level of use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first module provides the location information of both construction activities and the resources allocated to the activities, while the second module provides an easy access to construction drawing. Venkatraman and Yoong [4] described the development of a mobile facsimile solution called "ClikiFax" that can assist collaborative communications between parties on or away from the construction site, and reported that field testing and evaluation of the tool indicated its usefulness in conveying dynamic changes to site drawings and approvals at remote construction sites. Löfgren [12] presented a case study of utilizing mobile computing by one of the largest construction companies in Sweden to manage construction site operations in a pilot project.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected information data in the information system are analyzed to control future accidents by educating personnel with a required actions and arrangements. The more accurate observation reports, produce safer work site environment, this could be achieved by following a system of rewarding on reporting accurate information in the observation and reporting processes and this motivate the employees [13]. Site worker actively participating and engaging in continuously monitoring and collecting safety related information which gradually improve OHS management level in the field of construction.…”
Section: Introductionmentioning
confidence: 99%